2016
DOI: 10.1371/journal.pgen.1005927
|View full text |Cite
|
Sign up to set email alerts
|

The Oryza sativa Regulator HDR1 Associates with the Kinase OsK4 to Control Photoperiodic Flowering

Abstract: Rice is a facultative short-day plant (SDP), and the regulatory pathways for flowering time are conserved, but functionally modified, in Arabidopsis and rice. Heading date 1 (Hd1), an ortholog of Arabidopsis CONSTANS (CO), is a key regulator that suppresses flowering under long-day conditions (LDs), but promotes flowering under short-day conditions (SDs) by influencing the expression of the florigen gene Heading date 3a (Hd3a). Another key regulator, Early heading date 1 (Ehd1), is an evolutionarily unique gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…The expression profile of ShFT-A, over a 24-h cycle, was similar to FT profiles reported in rice (known as Hd3A and RFT1; Komiya et al 2008;Zhao et al 2012;Wang et al 2013;Lee and An 2015) and sorghum (known as CENTRORADIALES, CN; Yang et al 2014). In rice the expression peak of Hd3a and RFT1 was at the transition from dark to light in both photoperiod inductive and non-inductive conditions, however there was a higher level of expression under the inductive conditions (Izawa et al 2002;Lee et al 2016;Sun et al 2016). This expression profile for ShFT-A is an important base line to assess changes in expression during floral induction.…”
Section: Variations In Expression Of Genes That Are Associated With Tmentioning
confidence: 93%
“…The expression profile of ShFT-A, over a 24-h cycle, was similar to FT profiles reported in rice (known as Hd3A and RFT1; Komiya et al 2008;Zhao et al 2012;Wang et al 2013;Lee and An 2015) and sorghum (known as CENTRORADIALES, CN; Yang et al 2014). In rice the expression peak of Hd3a and RFT1 was at the transition from dark to light in both photoperiod inductive and non-inductive conditions, however there was a higher level of expression under the inductive conditions (Izawa et al 2002;Lee et al 2016;Sun et al 2016). This expression profile for ShFT-A is an important base line to assess changes in expression during floral induction.…”
Section: Variations In Expression Of Genes That Are Associated With Tmentioning
confidence: 93%
“…However, recent studies have shown that Hd1 represses the expression of Ehd1 in LD 33 , 34 , suggesting that Hd1 - and Ehd1 -mediated pathways are not always independent. In a recent report, Heading Date Repressor 1 (HDR1) and OsK4 were found to suppress heading date by upregulating Hd1 and downregulating Ehd1 , and the HDR1-OsK4 interaction complex can phosphorylate Hd1 35 .…”
Section: Introductionmentioning
confidence: 99%
“…MIP1A and MIP1B that repress owering by forming heterodimeric complexes that sequester CO and COL proteins into non-functional complexes [26] were also found to be up-regulated in BP. Another inconsistent transcriptional response for owering is up regulation of HEADING DATE REPRESSOR 1 (HDR1), a owering suppressor that up-regulates HD1 in LD conditions [61]. Again, inconsistent regulation of photoperiod pathway transcripts associated with owering in BP suggests down-stream signaling involvement in early bolting.…”
Section: Discussionmentioning
confidence: 99%